(Invited) Silicene: Silicon at the Two Dimensional Limit and Its Applications to Nanoelectronics. (18th August 2016) - Molle, Alessandro; Grazianetti, Carlo; Cinquanta, Eugenio
Abstract : In the realm of two dimensional materials for nanoelectronics, silicene, a honeycomb lattice of silicon atoms, has recently attracted an enormous interest for the semiconductor technology roadmap because of its intrinsic affinity with the silicon technology standards. The synthesis and the processing of silicene are non-trivial because of a number of physical constraints and technical bottlenecks that are here briefly mentioned. Attention is paid to outline technical strategies to easily handle silicene single layer and integrate it into functional devices.